Correction: Zn(ii), Cd(ii) and Hg(ii) saccharinate complexes with 2, 6-bis(2-benzimidazolyl)pyridine as promising anticancer agents in breast and lung cancer cell lines via ROS-induced apoptosis. Issue 25 (22nd June 2020) - Icsel, Ceyda; Yilmaz, Veysel T.; Aydinlik, Seyma; Aygun, Muhittin
Abstract : Correction for 'Zn(ii ), Cd(ii ) and Hg(ii ) saccharinate complexes with 2, 6-bis(2-benzimidazolyl)pyridine as promising anticancer agents in breast and lung cancer cell lines via ROS-induced apoptosis' by Ceyda Icsel et al., Dalton Trans., 2020, 49, 7842–7851, DOI: ; 10.1039/D0DT01535K .